2010
DOI: 10.1254/jphs.10100fp
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Anti-inflammatory Effects of the Ca2+/Calmodulin Antagonist CV-159 in Cultured Vascular Smooth Muscle Cells

Abstract: Abstract. CV-159 is a unique dihydropyridine Ca2+ antagonist with an anti-calmodulin (CaM) action. A pathogenic feature of atherosclerosis is vascular inflammatory change. In the present study, we examined whether CV-159 exerts protective effects on smooth muscle inflammatory responses. After pretreatment of rat mesenteric arterial smooth muscle cells (SMCs) with CV-159 (0.1 -10 μ M, 30 min), TNF-α (10 ng/ml) was applied for 20 min or 24 h. CV-159 inhibited TNF (24 h)-induced vascular cell adhesion molecule (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In the previous study, we showed that an antioxidant drug, N-acetyl l-cysteine inhibited TNF-induced expression of VCAM-1 and e-selectin, as well as activation of Akt, JNK, and p38, in cultured SMCs or endothelial cells. 14,15 In addition, we confirmed that the inhibitor of Akt, JNK, or p38 prevented TNF-induced expression of VCAM-1 or e-selectin. Collectively, our results indicate that DAPK3 mediates TNFinduced inflammation via induction of proinflammatory molecules (VCAM-1, e-selectin, and COX-2) through activation of ROS-dependent signals in cultured SMCs and endothelial cells.…”
Section: October 2012supporting
confidence: 64%
“…In the previous study, we showed that an antioxidant drug, N-acetyl l-cysteine inhibited TNF-induced expression of VCAM-1 and e-selectin, as well as activation of Akt, JNK, and p38, in cultured SMCs or endothelial cells. 14,15 In addition, we confirmed that the inhibitor of Akt, JNK, or p38 prevented TNF-induced expression of VCAM-1 or e-selectin. Collectively, our results indicate that DAPK3 mediates TNFinduced inflammation via induction of proinflammatory molecules (VCAM-1, e-selectin, and COX-2) through activation of ROS-dependent signals in cultured SMCs and endothelial cells.…”
Section: October 2012supporting
confidence: 64%
“…7). We have previously shown that antioxidant, N-acetyl L-cysteine prevented TNF-␣-induced ROS, VCAM-1, and phosphorylation of JNK and NF-B, suggesting that ROS mediates inflammatory responses in vascular SMCs and ECs (39,40). In addition, we showed that a CaM inhibitor, W-7, inhibited TNF-␣-induced activation of eEF2K, JNK, and NF-B as well as TNF-␣-induced expression of VCAM-1 and E-selectin in ECs (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The superior mesenteric artery was isolated. SMCs isolated from mesenteric artery by an explant method were cultured in DMEM supplemented with 10% FBS (Invitrogen, Carlsbad, CA) (40). Passages 4 to 20 SMCs at 80 to 90% confluence were growth arrested by incubating in DMEM containing 0.5% FBS for 24 h before stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting : Western blotting was performed as described previously [19, 29, 30, 32]. Protein lysates were obtained by homogenizing mesenteric artery with Triton-based lysis buffer (20 mM Tris-HCl (pH 7.5), 150 mM NaCl, 1 mM EDTA, 1 mM ethylene glycol tetraacetic acid, 1% Triton, 2.5 mM sodium pyrophosphate, 1 mM β-glycerophosphate, 1 mM Na 3 VO 4 and 1 µ g/m l leupeptin).…”
Section: Methodsmentioning
confidence: 99%